PENINGKATAN KUALITAS LAYANAN SEKOLAH SUNGAI MANGROVE GUNUNG ANYAR SURABAYA - Dani Puspitasari; Dewi Pertiwi; Mega Ekklesia Putrihadi (Universitas Mataram, 2023)
This community service aims to improve the quality of informal school services in the Gunung Anyar mangrove area, Surabaya. The activities that have been carried out consist of four stages: providing materials to support teaching and learning activities, training for teaching staff, dental health training for children, and administrative training for river school volunteers. A series of events were held in September – October 2023. The Gunung Anyar Margrove River School is an informal activity held every Sunday for children in the area around Magrove. This activity was initially initiated by a resident who cares about the environment and the teachers are volunteers. These teachers have no background as teachers and have received both formal and informal training. This community service targets providing equipment for volunteers. The training results showed increased knowledge regarding introducing child psychology and creative teaching in informal schools.